THE INFLUENCE OF THE REDUCTION DIETING ON RESTING METABOLIC RATE AND OXIDATIVE STRESS IN ATHLETES - Nestorova Brazhanska, Mihaela; Dejanova, Beti; Vidoevski, Filip (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Oxidative stress (OS) represents an imbalance between the production of reactive oxygen species (ROS) and the ability to detoxify the reactive intermediates, as well as the body's inability to provide adequate antioxidant defense. The aim of the study was to present the current data from the literature regarding influence of the reduction dieting on resting metabolic rate (RMR) and OS, in order to emphasize the need of dietary balance on sport performance and quality of life in athletes. By using the current literature of the Systematic Reviews databases such as Medline, the Cochrane Library, Scopus, Pubmed and Web of Science, the data were selected and analyzed. The effect that regular exercising has on OS is different, depending on age, sex, workout intensity and its duration. Moderate physical activity has a positive impact on OS, improving health, while intensive physical activity may lead to excessive production of ROS. Although the physical activity can lead to increased OS, it gives a positive stimulus for the endogenous antioxidative defense, according to the theory of hormesis. Athletes compared to the sedentary subjects have a higher percentage of muscle mass due to their active lifestyle. Higher percentage of muscle mass contributes to higher energy requirement. Although athletes strive to maintain the energy balance, reduction diets are considered to have a positive effect on OS. Experimental studies show that prolonged caloric deficit increases the average lifespan of rodents and other animal species. One of the hypotheses explaining the effect of slowing down the ageing process by a reduction diet is the decreased energetic expenditure, leading to decreased ROS production. Focused on OS decreasing and improving the sport performance, athletes need balanced nutrition, including reduction diets. Reduction diets that decrease RMR by a combination with moderate physical activity show a positive impact on OS, slowing down the ageing process, prolonging the lifespan.   Key words: oxidative stress, physical activity, reduction dieting, resting metabolic rate.